A novel aqueous dimethyl trisulfide formulation is effective at low doses against cyanide toxicity in non-anesthetized mice and rats. (2nd January 2022) - Lippner, D. S.; Hildenberger, D. M.; Rhoomes, M. O.; Winborn, J. N.; Dixon, H.; McDonough, J.; Rockwood, G. A.
Abstract: Background: Cyanide (CN) is a metabolic poison that is capable of intoxicating individuals through accidental or intentional means. With high concentration exposures, death can occur in minutes. In cases of mass casualty exposures, there is a need for a rapid-acting countermeasure capable of being administered in a short period of time in a pre-hospital setting to treat victims. Objective: These studies evaluate the safety and efficacy of a novel aqueous formulation of dimethyl trisulfide (DMTS) as an intramuscular (IM) CN countermeasure using non-anesthetized rodent models. Methods: Non-anesthetized rodents (mice and rats) were exposed to hydrogen cyanide (HCN) or potassium cyanide (KCN) along with immediate IM 10% DMTS treatment or vehicle treatment. Survival and other parameters, such as the time to recovery and assessment of clinical toxic signs (e.g., gasping, loss of righting reflex, convulsions, etc.), were quantified to determine the effectiveness of 10% DMTS treatment (12.5, 25, 75 mg/kg IM) compared to vehicle control treatment. A rat KCN delayed-treatment model with a 15-minute treatment delay was also utilized to simulate a real-life exposure/treatment scenario with 10% DMTS treatment. The stability of the 10% DMTS formulation was also assessed. Results: A 25 mg/kg IM dose of 10% DMTS exhibits potent efficacy against subcutaneous (SC) KCN challenge in both mice and rats and inhalational HCN exposure in mice. 10% DMTS treatment also shortens the time to recovery in rats using a delayed-treatment model. Conclusion: IM treatment with 10% DMTS improves survival and clinical outcomes in non-anesthetized rodent models of acute CN toxicity. Additionally, the use of an SC KCN delayed-treatment model in rats is advised to assess the performance of a candidate CN countermeasure in a more realistic exposure/treatment scenario.